1977
DOI: 10.7326/0003-4819-86-4-478
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Better Physician-Patient Communication

Abstract: Dismissal interviews were recorded between 48 patients and their physicians. Each patient took home a cassette containing this interview. About 3 months later, the patients received a questionnaire designed to assess the acceptability and usefulness of this method of communication. Most patients proved to have ready access to a cassette player. Their responses were highly favorable: 91% thought they were helped to understand the physician's discussion; 75% found it helpful to have their spouse or relatives lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1979
1979
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, at the follow-up interviews patients who had received the tape-recordings said they had found them of value. According to their self-reports, 13 of the 14 patients listened to their recordings at least once; and the 14th said that her husband and other members of her family had listened to the tape in order to understand her illness better. The tape-recordings were also used for this purpose by more than half the patients.…”
Section: Information Desired By Patientsmentioning
confidence: 99%
“…Nevertheless, at the follow-up interviews patients who had received the tape-recordings said they had found them of value. According to their self-reports, 13 of the 14 patients listened to their recordings at least once; and the 14th said that her husband and other members of her family had listened to the tape in order to understand her illness better. The tape-recordings were also used for this purpose by more than half the patients.…”
Section: Information Desired By Patientsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] We carried out a randomised single blind trial to compare the effects of providing or not providing mothers of babies in neonatal intensive care units with an audiotape of their conversations with the neonatologist.…”
Section: Introductionmentioning
confidence: 99%
“…1 Case management aims to improve outcomes in patients and, in particular, to reduce unplanned hospital admission. Systematic reviews of home based support for older people have drawn mixed conclusions from no overall impact on hospital admission 2 to reduced admission rates and costs, dependent on the system of care.…”
Section: Introductionmentioning
confidence: 99%
“…Butt [5] was the first to suggest that patients might benefit from being provided with an audio-tape of their consultation. A meta-analysis of audiocassettes of cancer consultations has reported that patients value consultation audio-tapes, and recent studies have yielded reports of increased satisfaction and recall of consultations if audio-tapes are provided.…”
Section: Discussionmentioning
confidence: 98%
“…All the consultations were audio-taped and analysed for doctor and patient behaviours. Provision of the question prompt sheet increased the number of patient questions about prognosis, although total question asking was unaffected [5]. In a subsequent similar study we investigated whether coaching in question asking [18] and provision of a question prompt sheet would intensify the impact; the question prompt sheet significantly increased the number of general questions and specific questions on prognosis and tests asked by cancer patients, but coaching had no additional impact [1].…”
Section: Consultation Audio-tapes As a Research Toolmentioning
confidence: 98%